If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -4) = 27 Reorder the terms: 3(-4 + 3x) = 27 (-4 * 3 + 3x * 3) = 27 (-12 + 9x) = 27 Solving -12 + 9x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 9x = 27 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = 27 + 12 9x = 27 + 12 Combine like terms: 27 + 12 = 39 9x = 39 Divide each side by '9'. x = 4.333333333 Simplifying x = 4.333333333
| 6(y+2)=42 | | -1-(-2)-7= | | 3(6x-1)=31 | | 8(4d-9)= | | 6x^2-53x=9 | | y/5=-15 | | t^2-8t+9=0 | | 5x+6x-(8x+5)= | | 3tgx=0 | | -3n+5=27 | | 19+8x-25=-7(3-x)+3x | | Senx=-1 | | tgx=0 | | w/2-30=53 | | y+5x-7=0 | | x+4/x-8 | | Y=(18+2x)/8 | | a^2/-3a-6 | | y/3=4 | | 4x^2+12x-7=9 | | n^2/-2n+8 | | 2x^2+25x-2000=0 | | n^2/-2n | | 9-3(x-2)=7+x | | 14/x=7/3 | | (18+2x)/8 | | 5/-8n | | 9x^3+35x^2-4x=0 | | y-3/y-1 | | b^2/7b+7 | | 30x+8x^2=0 | | 3(4+x)=x+16 |